Acute Thrombocytopenia Complicating the Initial Administration of Obinutuzumab: Is It More Frequent Than We Think? - Umut Yılmaz; Selin Küçükyurt; Muhlis Cem Ar; Ahmet Emre Eşkazan (Oncology and Therapy, 2024)
Abstract Thrombocytopenia has been reported more frequently with obinutuzumab in clinical trials where it was directly compared with rituximab. However, more significant than the frequency, a unique form of severe thrombocytopenia manifesting very early after the first obinutuzumab infusion has been published in case reports. To further explore this subject, we went through the records of our clinic to identify similar cases of obinutuzumab-induced acute thrombocytopenia (OIAT). Among 24 patients who received obinutuzumab outside of clinical trials, we recovered three cases with OIAT. This paper describes these three cases in detail, placing emphasis on the timing, severity, and the clinical course. Notably, all three patients developed severe OIAT within 5 days of their first obinutuzumab exposure, responded well to transfusion, and recovered within a few days without severe bleeding. None of the patients experienced a similar event in the second course of the obinutuzumab-based therapy. Our observations suggest that OIAT may be a frequent, possibly non-relapsing, and unique event that deserves more attention than it currently receives.